Do E-Service Machine Improve the Quality of Digital Customer Service in the Banking Sector? - Azizah, Siti Nur Fikriyyatul; Asri, Tri Mega; Utami, Rachma Bhakti (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2024)
Digital technology is increasingly expanding into banking by changing ordinary transaction models into digital transactions with the emergence of systems such as digital customer service. This article aims to determine the quality of digital customer service with the e-service machine media to the quality of banking services. This method identifies and describes the digital service quality of a private bank's sub-branch office in the City of Malang East Java on their e-service machine. The bank has developed the concept of digital transactions through digital machines which customers can use independently. The research method used is descriptive quantitative. The process of collecting data through questionnaires and literature studies. Based on the results and discussion in this scientific work, most respondents' responses indicate that the quality of digital customer service by e-service machine media is very satisfying to customers. Nevertheless, there is also a need for continuous evaluation and improvement to achieve maximum satisfaction for the customers. Keywords: E-Service; Digital Customer; Banking Service; Private Bank; Service Quality